2014
DOI: 10.1002/bjs.9613
|View full text |Cite
|
Sign up to set email alerts
|

Impact of faecal occult blood test screening on emergency admissions and short-term outcomes for colorectal cancer

Abstract: Background: Small studies have examined the effect of faecal occult blood test (FOBT) screening on the proportion of hospital admissions for colorectal cancer (CRC) classed as an emergency. This study aimed to examine this and short-term outcomes in persons invited for screening compared with a control group not invited. Methods: The invited group comprised all individuals invited between 1 April 2000 and 31 July 2007 in the Scottish arm of the UK demonstration pilot of FOBT, and subsequently diagnosed with CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…It therefore questions the impact that screening itself has had on overall emergency presentation in our geographical area. This is in keeping with a recently published cohort study, which has shown that emergency admissions are reduced when comparing participants and non-participants in screening; however, they remain similar comparing cohorts invited and not invited to screening ( Libby et al , 2014 ). Therefore, it appears that it is participation and not invitation that is the key determinant in reducing emergency admissions.…”
Section: Discussionsupporting
confidence: 89%
“…It therefore questions the impact that screening itself has had on overall emergency presentation in our geographical area. This is in keeping with a recently published cohort study, which has shown that emergency admissions are reduced when comparing participants and non-participants in screening; however, they remain similar comparing cohorts invited and not invited to screening ( Libby et al , 2014 ). Therefore, it appears that it is participation and not invitation that is the key determinant in reducing emergency admissions.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, screening programs, such as those that were put on hold during the slowdown period, are associated with lower rates of emergent presentation as tumours and pre-cancerous lesions are identified and removed at an earlier stage. ( 12 , 14–16 )…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, screening programs, such as those that were put on hold during the slowdown period, are associated with lower rates of emergent presentation as tumours and pre-cancerous lesions are identified and removed at an earlier stage. 12,[14][15][16] According to our data, patients in the post-slowdown cohort had tumours that were on average 25% larger than patients in the pre-slowdown cohort. The reduced number of patients receiving neoadjuvant therapy in the post-shutdown cohort may have marginally contributed to the differences in average tumour size between the two populations; however, the vast majority (78% of patients) did not receive neoadjuvant treatment.…”
Section: Discussionmentioning
confidence: 58%